PENINGKATAN KEMAMPUAN BERPIKIR KREATIF SISWA KELAS V DENGAN MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING - Endang Susanti; Sekar Dwi Ardianti; Denni Agung Santoso (STKIP Subang, 2023)
Learning outcomes at SDN 1 Woro class V still do not meet the minimum criteria. Judging from the average class after the test, there are 95% of students experiencing problems in solving problems. Thus resulting in students experiencing less than optimal thinking skills in the learning process. The purpose of this study is to use a Creative Problem Solving (CPS) learning model to improve the creative thinking ability of grade V SDN 1 Woro students. This quantitative research uses experimental methods. By consisting of class V students as many as 15 students as respondents. The tools used in collecting data are providing pretest and posttest questions. . Based on research that has been done, data were obtained that the creative thinking ability of grade V students increased after being given the influence of the Creative Problem Solving learning model, with an average of 77 which can be called effectively applied to mathematics subjects.